IMPROVING PURCHASE DECISIONS BY OPTIMIZING MARKETING MIX BY MEDIATION BY CONSUMER TRUST: A STUDY ON SUKABUMI RETAIL CONSUMERS - Muh Abdul Aziz; Alhidayatullah Alhidayatullah; Muhammad Khairul Amal (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
The development of retail businesses in Sukabumi City reflects increasingly intense competition, driven by consumers’ growing preferences for ease, convenience, and trust in the purchasing process. This competitive environment highlights the need for effective marketing strategies to both attract and retain customers. In this regard, the marketing mix and consumer trust serve as crucial factors influencing purchasing decisions. This study aims to examine the impact of the marketing mix (comprising product, price, place, and promotion) on purchase decisions, with trust acting as a mediating variable. Employing a quantitative approach, the study surveyed 100 active consumers using purposive sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software. The results revealed that product did not significantly affect trust (T = 0.023; P = 0.982) or purchase decisions (T = 0.824; P = 0.410). Price showed a significant influence on both trust (T = 1.985; P = 0.047) and purchase decisions (T = 4.526; P = 0.000). Place did not significantly impact trust (T = 0.399; P = 0.690) but did affect purchase decisions (T = 2.485; P = 0.013). Promotion had a significant effect on trust (T = 3.729; P = 0.000) but not on purchase decisions (T = 1.720; P = 0.086). Additionally, trust significantly influenced purchase decisions (T = 2.626; P = 0.009). These findings emphasize that appropriate strategies in pricing, placement, and promotion can foster consumer trust and positively influence purchasing behavior Keywords: Product; Price; Place; Promotion; Trust; Purchase Decision